2015
DOI: 10.1111/1750-3841.12974
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Green Route for Room‐Temperature Synthesis of Gold Nanoparticles and Selective Colorimetric Detection of Cysteine

Abstract: Gold nanoparticles (AuNPs) were synthesized at room temperature following a simple, rapid, and green route using fresh-squeezed apple juice as a reducing reagent. The optimal AuNPs, based on the particle color, stability, and color change suitable for colorimetric detection of cysteine (Cys), are synthesized using 5 mL of 10% apple juice, 1 mL of 10 mM gold precursor solution, and 1 mL of 0.1 M NaOH. Under this set of parameters, the AuNPs are synthesized within 30 min at room temperature. The average size (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Alginate is a non-toxic, biocompatible, and inexpensive polysaccharide; it is widely used in pharmaceutical and biomedical applications (Boland et al 2007;Xu et al 2010). The AuNPs are highly biocompatible and possess distinct surface plasmon properties (Bagci et al 2015;Ghosh et al 2008;Guan et al 2015;Lu et al 2016;Wang et al 2015b;Wei et al 2015;Zhang et al 2015). Furthermore, our results indicate, contrary to Einstein-Batchelor viscosity law, that in situ synthesis of AuNPs in alginate solution lowers its viscosity, as had been reported for some other polymeric solutions with nanoparticles addition (Jain et al 2008;Mangal et al 2015).…”
Section: Introductionsupporting
confidence: 76%
“…Alginate is a non-toxic, biocompatible, and inexpensive polysaccharide; it is widely used in pharmaceutical and biomedical applications (Boland et al 2007;Xu et al 2010). The AuNPs are highly biocompatible and possess distinct surface plasmon properties (Bagci et al 2015;Ghosh et al 2008;Guan et al 2015;Lu et al 2016;Wang et al 2015b;Wei et al 2015;Zhang et al 2015). Furthermore, our results indicate, contrary to Einstein-Batchelor viscosity law, that in situ synthesis of AuNPs in alginate solution lowers its viscosity, as had been reported for some other polymeric solutions with nanoparticles addition (Jain et al 2008;Mangal et al 2015).…”
Section: Introductionsupporting
confidence: 76%
“…Biological methods for nanoparticle synthesis using microorganisms, enzymes, vitamins, sugar, and biodegradable polymers of plant or animal origin have been suggested as possible ecofriendly alternatives to chemical and physical methods. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that many natural compounds, such as those derived from fungi, algae, bacteria, and plants, were used in green synthesis of AuNPs [7,8,9,10]. These natural compounds-mediated procedures for synthesis of AuNPs represent advantages over conventional chemical and physical methods, as they are simply, low-cost, energy-efficient, and nontoxic green routes [11,12,13,14]. In this regard, we focused our attention on natural polysaccharide extracted from seaweed, which is a proven source of bioactive compounds [15].…”
Section: Introductionmentioning
confidence: 99%